Application of Aeroponics Techniques on The Growth of Spinach (Amaranthus sp) (J-AGENT (Journal of Agricultural Engineering and Technology), 2024)
Aeroponics is a method of farming that uses air to spray nutrient solutions on the roots of plants.This study was to determine the performance, and productivity of the application of aeroponictechniques. This study used an experimental method with three aeroponic installations, and typesof rockwool, cocopeat, and husk charcoal growth media, and nozzle sizes 0.1 mm, 0.4 mm, and0.6 mm. Spraying time in the morning - afternoon is 30 minutes on, and 30 minutes off, while atnight, it is 15 minutes on, and 45 minutes off. Parameters observed were pump, and nozzledischarge, nozzle outpouring uniformity value, electrical conductivity (EC), acidity (pH), solutiontemperature, ambient temperature, plant water consumption, air humidity, light intensity, plantgrowth, and plant productivity. The results of the observations were analyzed using statisticalanalysis, and two-factor ANOVA testing. The results showed that the range of pump dischargevalues was 3.58 ml/second – 3.676 ml/second, and nozzle discharge values of 0.1 mm, 0.4 mm,and 0.6 mm were 0.303 ml/second, 0.975 ml/second, and 1.225 ml/second. The good uniformityof nozzle outpouring is 0.1 mm (97.17%) nozzle. The value (EC) during the growth period was1.0 mS/cm – 2.5 mS/cm, the result of measurement of acidity (pH) was 5.7 – 7.5. The temperatureof the nutrient solution is 26℃ - 37℃ while the ambient temperature reaches 27℃ - 39℃. Thehighest plant water consumption is 11.32 liters, and the humidity reaches 40% - 86%. The highestlight intensity occurs outside the greenhouse. The results of the ANOVA test on the size of thenozzle, and the growth media affect plant growth and productivity. 0.1 mm nozzle has optimalspraying, and good growth media are husk charcoal, and rockwool.
Keywords: aeroponic; growth media; nozzle